2002
DOI: 10.1111/1467-7687.00225
|View full text |Cite
|
Sign up to set email alerts
|

Atypical development of language and social communication in toddlers with Williams syndrome

Abstract: Williams syndrome (WS) is a genetic disorder which results in an uneven cognitive profile. Despite superior language compared to other syndromes in the phenotypic outcome, toddlers with WS are as delayed in their language onset and early linguistic development as are toddlers with other syndromes. The cause of this delay in WS is as yet unknown. In a series of experiments, we examined whether atypical socio-interactive precursors to language could contribute to the explanation of the late language onset and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0
14

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(123 citation statements)
references
References 42 publications
4
105
0
14
Order By: Relevance
“…Brown et al (2003) also found evidence of problems planning saccades and shifting attention. Infants also show attention shifting difficulties during triadic interactions, relating attention skills to social cognition (see Laing et al 2002). It seems likely that problems modulating attention exist throughout the developmental spectrum and therefore it makes sense that they may also link to gaze behaviours associated with the disorder.…”
mentioning
confidence: 99%
“…Brown et al (2003) also found evidence of problems planning saccades and shifting attention. Infants also show attention shifting difficulties during triadic interactions, relating attention skills to social cognition (see Laing et al 2002). It seems likely that problems modulating attention exist throughout the developmental spectrum and therefore it makes sense that they may also link to gaze behaviours associated with the disorder.…”
mentioning
confidence: 99%
“…Jones et al 2000), individuals with WS also have some social difficulties. For instance, they have difficulties in triadic social interaction (Laing et al 2002) and in making and sustaining friendships particularly with their peers (Gosch and Pankau 1994). Moreover, they have poor social judgement (Gosch and Pankau 1994) and often lack of social inhibition .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, social behaviour in WS may also be maladapted and characterized by overfriendliness, oversensitivity and poor-peer relations (e.g. Laing et al 2002). Knowledge of the mechanisms implicated in this unusual social behaviour of WS suggests far more complexity than was originally envisioned.…”
Section: Introductionmentioning
confidence: 99%
“…In typical development, infants are initially drawn to face-like visual stimuli, progressively coming to devote more discriminating attention to specifically human faces in contrast to other face-like stimuli as well as to other objects. Infants with WS share this preference for face-like stimuli, even showing a disproportionate interest in faces compared to that of normal controls (Mervis and Bertrand 1997;Bellugi et al 2000;Laing et al 2002). By contrast, this bias seems to be completely lacking in individuals with ASD.…”
Section: Testing the Assumptions Of Ultra-cnp-evidence From Developmementioning
confidence: 98%